Nigella sativa meal alleviates injury against benzo[a]pyrene exposures in broilers - Latif, I. K. (Universiti Putra Malaysia Press, 2011)
This study was conducted to evaluate the effects of Nigella sativa (Ns) meal on such influences of Benzo[a] Pyrene (BaP) on the broilers performance, pulmonary index (PI), and histopathological changes. Chicks were assigned into four equal groups, namely as controls, Ns, BaP and BaP with Ns. Six birds were sacrificed at days 7, 14, 21, and 35. The results revealed that there were significant decreases (p<0.05) in the mean body weight (BW) values and body weight gain (BWG) in the BaP alone group. Pulmonary weight (PW) and index increased (p<0.05) in the same group compared to the control groups. Pulmonary morphology showed heavy infiltration and denudation of ciliated epithelium in the trachea, with infiltration by polymorphonuclear and mononuclear cells in the parabronchi of the lung, in the BaP exposed chickens. Nigella sativa (Ns) supplementation significantly alleviated these alterations, and thereby showing a potent anti-inflammatory effect after 14 days in the treated group. A key finding from this study is that BaP triggers inflammatory disorders and this transient effect is believed to be fatal if an infection occurs warranting a reassessment of the health status on exposure, and Ns was found to be helpful in alleviating such effects in broiler chickens.